2007
DOI: 10.1002/icd.510
|View full text |Cite
|
Sign up to set email alerts
|

Infant touching behaviour during mother–infant face‐to‐face interactions

Abstract: The study of infant communication during mother-infant interactions has largely focused on infants' distal behaviours, while neglecting their more proximal behaviours, such as touch. Yet, touch is an important modality through which infants and mothers communicate; it is also a vital means through which infants self-regulate and explore their surroundings. The present study was designed to investigate the touching behaviours of 44, 5 1/2-month-old, healthy, full-term infants during face-to-face mother-infant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 36 publications
1
40
0
4
Order By: Relevance
“…Previous investigations have documented that infants rely on several regulatory strategies to effectively maintain or reduce their arousal (Bridges, Denham, & Ganiban, ; Kopp, ; Rothbart, Ziaie, & O'Boyle, ). For example, results from studies have demonstrated that across periods of the SF procedure, infants engage in a number of self‐regulatory behaviours (e.g., gaze aversion, attention‐seeking, exploration, and self‐soothing), but the durations of these behaviours change when the regulatory support of caregivers becomes unavailable during the SF period (Braungart‐Rieker et al, ; Moszkowski & Stack, ; Weinberg & Tronick, ). In addition, evidence suggests a clear association between infants' self‐regulatory strategies and infants' current emotional and attentional states.…”
Section: Brief Operational Definitions For the Functions Of Touch Scamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have documented that infants rely on several regulatory strategies to effectively maintain or reduce their arousal (Bridges, Denham, & Ganiban, ; Kopp, ; Rothbart, Ziaie, & O'Boyle, ). For example, results from studies have demonstrated that across periods of the SF procedure, infants engage in a number of self‐regulatory behaviours (e.g., gaze aversion, attention‐seeking, exploration, and self‐soothing), but the durations of these behaviours change when the regulatory support of caregivers becomes unavailable during the SF period (Braungart‐Rieker et al, ; Moszkowski & Stack, ; Weinberg & Tronick, ). In addition, evidence suggests a clear association between infants' self‐regulatory strategies and infants' current emotional and attentional states.…”
Section: Brief Operational Definitions For the Functions Of Touch Scamentioning
confidence: 99%
“…There is consistent evidence that infants respond to the SF period by displaying a 'signature' SF effect that consists of a decrease in positive affect, with an increase in gazing away from mothers, fretting, and neutral affect (see Adamson & Frick, 2003;Mesman, van Ijzendoorn, & Bakermans-Kranenburg, 2009). Furthermore, as a means to cope with the distress associated with the SF period, infants increase their use of self-regulatory behaviours, such as self-touch, exploration, and gaze aversion (e.g., Manian & Bornstein, 2009;Moszkowski & Stack, 2007;Weinberg & Tronick, 1996). Such responses are an indication that in the context of maternal emotional unresponsiveness, infants resort to using their own internal regulatory mechanisms (Braungart-Rieker, Garwood, Powers, & Natoro, 1998;Gianino & Tronick, 1988).…”
mentioning
confidence: 99%
“…After delivery, touch becomes an important channel of communication during mother–infant interactions (De Chateau, 1976; Tronick, 1995; Stack, 2004; Moszkowski and Stack, 2007; Jean and Stack, 2009; Stack et al, unpublished). It occurs more than the 55% of time and communicates security and tenderness, reducing infants’ distress and promoting emotional regulation (Stack and Muir, 1990, 1992; Weiss et al, 2000; Jean et al, 2004; Jean and Stack, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Additionally, Moszkowski and Stack (2007) found that infants tried to touch their mothers more in the normal interactions than during the maternal still-face episodes. However, Dibiasi and Einspieler (2002) failed to find an interaction between acoustic stimulation and spontaneous arm movements in 12-week-old infants.…”
Section: Introductionmentioning
confidence: 99%